APPLICATION OF CARBON TAX ON TAXPAYERS - Murdiansyah, Isnan; Salsabela, Novita; Lestari, Heppy Widya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
The increase in carbon emissions every year is a problem on a global scale that is increasingly worrying. By ratifying the Paris Agreement, Indonesia is committed to participating in mitigating carbon emissions in the world. To prove this commitment, the Indonesian government implemented a fiscal policy, namely the carbon tax policy. The purpose of this study is to analyze how much influence the implementation of the carbon tax policy has on taxpayer readiness. In this study, there are two types of data, namely primary data obtained through field studies with questionnaires and secondary data obtained through literature studies and other references relevant to the research topic. The quantitative research method with simple linear regression analysis was chosen by the researcher to determine the effect of the variable implementation of carbon tax on the variable of taxpayer readiness. The results of the study indicate that the implementation of the carbon tax policy has a negative effect on taxpayer readiness. This means that if the carbon tax policy is implemented, it will have an effect on increasing taxpayer readiness. With this research, it is hoped that it can be used as material for evaluation and government considerations in the perspective of taxpayers in relation to the implementation of carbon tax policies